EKUALISASI SPT MASA PPN DENGAN SPT TAHUNAN PPh UNTUK MENGANTISIPASI POTENSI PEMERIKSAAN PAJAK - Asrofi Langgeng Noerman Syah (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2023)
This study aims to determine the equalization of the VAT Periodic Tax Return with the Annual IncomeTax Return to anticipate potential tax audits on CV. XYZ Tegal Regency. Equalization is needed to findout the difference between buying and selling and knowing the cause of the difference stated in theLetter of Request for Explanation of Data and/or Information (SP2DK) received by CV. XYZ from KPPPratama Tegal. By doing equalization on CV. XYZ, the company can find out where the error is and tobe a reference in carrying out its tax obligations in the future. This study uses a quantitative descriptiveanalysis technique with the method of analyzing the level of balance between the taxes reported in theVAT Periodic Tax Return and the financial statements. Sources of data obtained from the study ofdocumentation, interviews and literature. The results of this study indicate that the difference in thecompany's turnover reported is due to the sale or delivery of goods in retail which is not subject to VATso that it is not recorded in the VAT Periodic Tax Return, there are sales made free of charge to certainparties but no tax invoices and tax administration are made. XYZ who is less orderly, including fromthe transaction partner.